Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017; Session "Ethics" - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 2nd Congress of joint European Neonatal Societies (jENS 2017); Venice (Italy); October 31-November 4, 2017 58th ESPR Annual Meeting, 7th International Congress of UENPS, 3rd International Congress of EFCNI ORGANIZING INSTITUTIONS European Society for Paediatric Research (ESPR), European Society for Neonatology (ESN), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI) ORGANIZING COMMITTEE Luc Zimmermann (President of ESPR), Morten Breindahl (President of ESN), Manuel Sánchez Luna (President of UENPS), Silke Mader (Chairwoman of the Executive Board and Co-Founder of EFCNI) SCIENTIFIC COMMITTEE Virgilio P. Carnielli (Congress President Chair), Pierre Gressens (Past Scientific President), Umberto Simeoni, Manon Benders, Neil Marlow, Ola D. Saugstad, Petra Hüppi, Agnes van den Hoogen Session "Ethics" ABS 1. THE DELIVERY OF BAD NEWS: A ONE OR 2-STEP APPROACH? THE CASE FOR TRISOMY 21 • M.S. Schimmel, M.Y. Kassirer, H.M. Towers ABS 2. NEONATAL ORGAN DONATION: A POTENTIAL NEW DONOR SOURCE FOR CELL AND ORGAN TRANSPLANTATION • C. Jorns, E. Henckel, G. Nowak, A. Karadagi, T. Kjellin, E. Bluhme, Ö. Jynge, M. Hending, A. Croon, M. Söderström, B. Fischler, A. Nemeth, R. Gramignoli, S. Strom, E. Ellis, B. Hallberg ABS 3. HEALTH CARE PROFESSIONALS' AND PARENTS' ATTITUDES TOWARD PARENTAL AUTONOMY AND THE BEST INTEREST OF THE EXTREME PRETERM INFANT: A NATIONAL STUDY IN SWITZERLAND • M. Hendriks, H. Bucher, S. Klein, R. Baumann-Holzle, J. Streuli, J. Fauchère ABS 4. CHANGING PARENTAL PERCEPTIONS IN TRISOMIES - A POTENTIAL ETHICAL DILEMMA FOR NEONATOLOGISTS? • E. Simons, P. Nath, P. Parthasarathy ABS 5. INGEBORG SYLLM-RAPOPORT (1912-2017) - AN EXEMPLARY LIFE FOR CHILDREN AND PAEDIATRICS • H. Sallmon, R.R. Wauer, C.C. Roehr ABS 6. RETROSPECTIVE ANALYSES OF PARENTAL COUNSELING AND DECISION MAKING FOR EXTREME PRETERM BIRTH IN A TERTIARY DUTCH PERINATAL CENTER • E. de Booij, J. de Boer, A. Eggink, I. Reiss, S.H.P. Simons, I.A. Brussé